Development of innovative teaching strategies to stimulate the learning of the English language - Milton Steeven Chiriboga Pantusin,; Víctor Reinal Jama Zambrano, (Dominio de las Ciencias, 2025)
The development of innovative teaching strategies is crucial to enhancing the effectiveness of English language learning in a rapidly evolving educational landscape. These strategies aim to not only improve fluency and comprehension but also empower students with critical thinking and communication skills necessary for global competence. A mixed-approach technique with a descriptive orientation was used to collect data through field research employing instruments that allow for a comprehensive review of the subject from several perspectives. This study analyzes the development of innovative teaching strategies to stimulate the learning of the English language. By integrating technology, such as digital learning platforms, gamification, and virtual reality, alongside traditional and interactive methods like storytelling, task-based learning, and collaborative activities, educators can address diverse learning styles and needs. This approach includes surveys, observation sheets, and interviews. The findings emphasize that innovative approaches not only enhance linguistic competence but also encourage critical thinking, creativity, and global communication skills, making them indispensable in modern English language education. It can be concluded that the development of innovative teaching strategies plays a crucial role in enhancing the learning of the English language, addressing both the challenges and opportunities of modern education. Teachers must constantly change and improve their approaches to guarantee that students are equipped with the skills, motivation, and knowledge required for success in an increasingly globalized and digital world. By including varied and forward-looking approaches, they can create more interesting, inclusive, and effective language learning experiences for students and educators.